Change in emotional self‐concept following socio‐cognitive training relates to structural plasticity of the prefrontal cortex. Issue 4 (13th March 2018) - Lumma, Anna‐Lena; Valk, Sofie L.; Böckler, Anne; Vrtička, Pascal; Singer, Tania
Abstract: Introduction: Self‐referential processing is a key component of the emotional self‐concept. Previous studies have shown that emotional self‐referential processing is related to structure and function of cortical midline areas such as medial prefrontal cortex (mPFC), and that it can be altered on a behavioral level by specific mental training practices. However, it remains unknown how behavioral training‐related change in emotional self‐concept content relates to structural plasticity. Methods: To address this issue, we examined the relationship between training‐induced change in participant's emotional self‐concept measured through emotional word use in the Twenty Statement Test and change in cortical thickness in the context of a large‐scale longitudinal mental training study called the ReSource Project . Results: Based on prior behavioral findings showing increased emotional word use particularly after socio‐cognitive training targeting perspective‐taking capacities, this study extended these results by revealing that individual differences in the degree to which participants changed their emotional self‐concept after training was positively related to cortical thickness change in right mPFC extending to dorsolateral PFC (dlPFC). Furthermore, increased self‐related negative emotional word use after training was positively associated with cortical thickness change in left pars orbitalis and bilateral dlPFC. Conclusions: Our findings reveal training‐related structural brain change in regions known to be involved in self‐referential processing and cognitive control, and could indicate a relationship between restructuring of the emotional self‐concept content as well as reappraisal of negative aspects and cortical thickness change. As such, our findings can guide the development of psychological interventions targeted to alter specific facets of the self‐concept. Abstract : The goal of the current study, which was conducted within a large‐scale longitudinal mental training study called the ReSource Project, was to investigate whether behavioral training‐related change in emotional self‐concept content relates to plasticity in brain structure. Our findings show that a 3‐month socio‐cognitive mental training intervention can induce change in emotional self‐descriptions and is related to structural brain change in regions such as the mPFC, dlPFC, and pars orbitalis known to be involved in self‐referential processing, emotion regulation, and cognitive control. Overall, these findings can guide future development of psychological interventions targeted to alter specific facets of the self‐concept.